STRATEGI GURU SKI DALAM PENINGKATAN MOTIVASI BELAJAR SEJARAH KEBUDAYAAN ISLAM DI MDTA MUHAMMADIYAH SUNGAI BULUAH CINGKARIANG KEC. BANUHAMPU KAB. AGAM - Zulfahmi Ahmad; Pendi Hasibuan (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted because it was motivated by the low motivation to learn Islamic Cultural History, with the reason that learning the history of Islamic culture in learning students more accepted or accommodated what was conveyed by the teacher without playing an active role, coupled with teaching methods that more often used the lecture method which resulted in students become passive and sleepy. To collect data, researchers conducted interviews with teachers and students followed by observing directly the process of learning the history of Islamic culture. From the research that has been done, it can be concluded that in order to increase motivation to learn the history of Islamic culture, PAI teachers have a strategy by using various teaching methods, such as lectures, discussions, questions and answers, and group work. Apart from this strategy, the teacher also uses interesting media so that students' attention is focused on learning, the teacher also gives rewards to students who are successful in learning and the teacher also gives punishment to students who are lazy. In the teaching process the teacher also experiences obstacles in increasing learning motivation, namely the lack of interest of students in SKI subjects or learning materials, the absence of handbooks for students, class conditions, family conditions of students, even the condition of the students. alone. However, all of this can be overcome by the teacher by growing students' interest in learning about SKI lessons by telling exemplary stories, providing photocopies of important material the day before discussing the material, giving warnings or being advised if they cannot be advised, the teacher gives punishment in the form of rote memorization and assigns assignments. provide an appeal to parents of students to continue to pay attention and supervision to these students, to approach students who are experiencing problems. Keyword: Teacher Strategy, Learning Motivation